Parapelvic kidney cysts: a distinguishing feature with high prevalence in Fabry disease - Ries, Markus; Bove Bettis, Karen E.; Choyke, Peter; Kopp, Jeffrey B.; Austin, Howard A.; Brady, Roscoe Owen; Schiffmann, Raphael (Kidney international, 2015)
Parapelvic kidney cysts: A distinguishing feature with high prevalence in Fabry disease. - Backgound - Fabry disease is an X-linked generalized progressive debilitating lysosomal storage disorder. The disease usually manifests in childhood, but the diagnosis is often made following the occurrence of late-stage complications such as progressive kidney failure. In order to identify key novel renal diagnostic imaging features of Fabry disease, we conducted a cross sectional case-control study of kidney involvement in patients with Fabry disease. - Methods - Twenty-four patients (mean age 36.1 ± 8.1 years, median 37 years, range 20 to 48 years) with chronic neuropathic pain who were enrolled in an enzyme replacement trial underwent prospective renal imaging evaluation with magnetic resonance imaging (MRI) and computed tomography (CT) at the National Institutes of Health, Bethesda, Maryland. We concurrently enrolled 19 age-matched healthy controls (mean age 34.6 ± 12.0 years, median 33 years, range 18 to 61 years). The presence and localization of kidney cysts as well as the ratio of the signal intensity between medulla and cortex were determined. - Results - Fifty percent of the Fabry disease patients had renal sinus cysts, compared to one individual (7%) in the control group. The ratio of the signal intensity between medulla and cortex on T2-weighted scans in Fabry disease patients with sinus cysts was elevated compared with Fabry disease patients without cysts (P = 0.0083), and elevated in Fabry disease patients without cysts compared with normal controls without cysts (P = 0.0173). - Conclusion - The finding of multiple renal sinus cysts in the workup of a patient with kidney disease patient should strongly suggest the consideration of Fabry disease in the differential diagnosis. The cause of such cysts in Fabry disease remains to be elaborated.
Gesehen am 16.05.2019